(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Ali the localities with Upper San Cassiano Formation Brachiopod faunas present in the Ampezzan valley are described. The genus Diplospirella Bittner, 1890, namely, the species Diplospirella wissmanni (Miinster), Diplospirella sufflata (Miinster), and Diplospirella aureolata (Cornalia) are re-examined. Analysis under SEM and of several transverse sections has revealed new morphologic elements: Cardinal lamina and Cardinal pit in the cardinalia; a complex jugum; the absence of a skeletal connection between spiralia and crura. The proposal advanced by Dagys (1974) attributing the genus Diplospirella to the order Athyridida is accepted.